Effect of environmental factors on postoperative recurrent primary spontaneous pneumothorax: a case-crossover study - Liu, Yu-Wei; Kao, Chieh-Ni; Ho, Chi-Chang; Chou, Shah-Hwa; Chen, Pau-Chung; Huang, Shu-Hung (Respiratory research, 2025)
Surgery is one of the preferred primary treatments for primary spontaneous pneumothorax (PSP); however, postoperative recurrent pneumothorax (PORP), defined as recurrence on the same side, occurs in 3-13% of cases. While environmental factors have been implicated in PSP occurrence, their role in PORP remains unclear. This study aimed to investigate the impact of environmental factors on the onset of PSP and PORP in the same patient population. Between 2009 and 2019, a total of 442 patients (aged ≤ 40 years) underwent 486 surgeries for PSP, with 43 patients (8.8%) experiencing a first PORP. Management of PORP included reoperation (29 patients), pleural drainage with chemical pleurodesis (4 patients), and conservative observation (10 patients). In this case-crossover study, the day of symptom onset for PSP and PORP was designated as the "case day." To evaluate potential lag effects, the days leading up to symptom onset, ranging from 1 day prior (lag day 1) to 7 days prior (lag day 7), were also analyzed as "case days." Unidirectional matched control days were selected 14-21 days before the case day (lag day 0). Elevated PM levels were significantly associated with PSP onset at lag day 0 and lag day 1, with increased odds observed at these time points (p = 0.04 and p = 0.02, respectively). No such association was found for PORP patients. Meteorological factors did not appear to influence PSP or PORP risk. Seasonally, both the PSP incidence and the PORP incidence were significantly greater in autumn and spring than in summer and winter (p < 0.001). PSP and PORP demonstrate seasonal clustering, with higher incidences in autumn and spring. Elevated PM levels appear to contribute to PSP onset but not PORP, suggesting that air pollution may be a potential trigger for PSP. Further research is needed to clarify environmental influences and optimize tailored management strategies. Not applicable.